Flipped Classroom adapted to the ARCS Model of Motivation and applied to a Physics Course - Aşıksoy, Gülsüm; Özdamlı, Fezile (Eurasia Journal of Mathematics, Science and Technology Education, 2016)
This study aims to determine the effect on the achievement, motivation and self-sufficiency of students of the flipped classroom approach adapted to Keller's ARCS (Attention, Relevance, Confidence and Satisfaction) motivation model and applied to a physics course. The study involved 66 students divided into two classes of a physics course. The first class used the traditional lecture format while the flipped classroom model was used in the second. The research data were obtained via the physics concept test, motivation questionnaire, physics self-sufficiency scale and semi-structured interviews. It was found that the experimental group students were achieve more than the students in the control group. An increase in motivation and self-sufficiency of the students in the experimental group was identified as well. Thereafter, semi-structured interviews were carried out with students of the experimental group. It was found that they had positive opinions regarding the flipped classroom approach.